Reflections and concerns about comparative education in Latin America and Colombia (2022)
Comparative Education in Latin America and Colombia, observed from its historical journey, and accompanied by different positions, allows us to reflect on those educational experiences that have passed through the country, as well as on how this Education reaches the continent and the impact it has for the region and the nation. However, the objective of this document is to reflect on actions, strategies and discussions raised around comparative education in Latin America and Colombia in recent history. In the same way, make visible the theoretical production on comparative education, in addition to understanding what happens with the discipline from the reflections that have been made about it historically, and what happens today with the educational systems in Colombia. A main conclusion, and supported by Acosta, Felicitas, & Ruiz, Guillermo, is that the current challenges of Comparative Education allow us to appreciate what the terms of the discussion are today, so it is essential to make discussions thinking about the real scenarios of each social context.